Among digitized manuscripts : philology, codicology, paleography in a digital world - Lit, L. W. C. van (Lambertus Willem Cornelis) (Handbook of oriental studies = Handbuch der Orientalistik. Section one, The Near and Middle East, 2020)
"Working with manuscripts has become a digital affair. But, are there downsides to digital photos? And how can you take advantage of the incredible computing power you have literally at your fingertips? Cornelis van Lit explains in detail what happens when manuscript studies meets digital humanities. In Among Digitized Manuscripts you will learn why it is important to include a note on the photo quality in your codicological description, how to draw, collect, and publish glyphs of paleographic interest, what standards (such as TEI and IIIF) to abide by when transcribing a text, how to write custom software for image recognition, and much more. The leading principle is that learning a little about computers will already be of great benefit"--